2014
DOI: 10.1001/jamadermatol.2013.7530
|View full text |Cite
|
Sign up to set email alerts
|

Agminated Pyogenic Granuloma–Like Growth Arising in a Congenital Hemangioma

Abstract: several months. Our patient was without hydroxyurea for 2 months and showed no improvement. Only after the hydroxyurea therapy was discontinued permanently was her ulcer finally able to resolve with medical and surgical intervention. Another complicating factor in our patient's wound healing was the immunosuppressive effects of the prednisone and azathioprine, which likely led to intermittent superinfection and prevented the ulcer from healing on its own. Why does hydroxyurea cause cutaneous ulceration? Almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…This may have been caused by pyogenic granuloma, a complication resulting from infection at the biopsy site. Symptoms of pyogenic granuloma include friable granulation tissue‐like changes and hemorrhage, and the histopathological findings reveal granulomatous microvascular proliferation, which is consistent with the present case 7 . To date, only two cases of pyogenic granuloma complicating congenital hemangioma have been reported 7,8 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This may have been caused by pyogenic granuloma, a complication resulting from infection at the biopsy site. Symptoms of pyogenic granuloma include friable granulation tissue‐like changes and hemorrhage, and the histopathological findings reveal granulomatous microvascular proliferation, which is consistent with the present case 7 . To date, only two cases of pyogenic granuloma complicating congenital hemangioma have been reported 7,8 .…”
Section: Discussionsupporting
confidence: 89%
“…Symptoms of pyogenic granuloma include friable granulation tissue‐like changes and hemorrhage, and the histopathological findings reveal granulomatous microvascular proliferation, which is consistent with the present case. 7 To date, only two cases of pyogenic granuloma complicating congenital hemangioma have been reported. 7 , 8 In one case, friable granulation tissue‐like changes with bleeding spontaneously developed within an infant's congenital hemangioma located on the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the relatively common coexistence of vascular tumors and vascular malformations, such as pyogenic granuloma (PG) arising with CM and PG arising in a CH [ 9 , 10 ]. Combined capillary-venous-lymphatic malformations without overgrowth in patients with Klippel-Trénaunay syndrome have been reported [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some lesions may ulcerate, bleed or leave a scar. Other complications include pyogenic granuloma-like growth [7], a life threatening hemorrhage and thrombocytopenia [1,8]. Although most hemangiomas are isolated anomalies, several studies have reported that hemangiomas may run in families as an autosomal dominant trait suggesting the involvement of causative genetic factors [9].…”
Section: Discussionmentioning
confidence: 99%